Catheter‐Related Complications in Cancer Patients on Home Parenteral Nutrition: A Prospective Study of Over 51, 000 Catheter Days. Issue 3 (20th September 2012) - Cotogni, Paolo; Pittiruti, Mauro; Barbero, Cristina; Monge, Taira; Palmo, Augusta; Boggio Bertinet, Daniela
Abstract : Background : Although home parenteral nutrition (HPN) is often indicated in cancer patients, many physicians are concerned about the risks potentially associated with the use of central venous access devices (VADs) in these patients. The aim of this prospective study was to investigate the actual incidence of VAD‐related complications in cancer patients on HPN. Methods : All adult cancer patient candidates for VAD insertion and HPN were enrolled. The incidence of complications associated with 4 types of VADs (peripherally inserted central catheter [PICC], Hohn catheter, tunneled Groshong catheter, and port) was investigated, as well as the most significant risk factors. Results : Two hundred eighty‐nine VADs in 254 patients were studied, for a total of 51, 308 catheter‐days. The incidence of catheter‐related bloodstream infections (CRBSIs) was low (0.35/1000 catheter‐days), particularly for PICCs (0/1000; P < .01 vs Hohn and tunneled catheters) and for ports (0.19/1000; P < .01 vs Hohn and P < .05 vs tunneled catheters). Mechanical complications were uncommon (0.8/1000), as was VAD‐related venous thrombosis (0.06/1000). Ultrasound‐guided venipuncture was associated with a decreased risk of CRBSI ( P < .04) and thrombosis ( P < .001). VAD securement using sutureless devices reduced the risk of CRBSI and dislocation ( P < .001). Hohn catheters had no advantage over PICCs (higher complication rate and shorter dwell time; P < .001). Conclusions : In cancer patients, HPN can be safely carried out with a low incidence of complications. Also, VADs are not equal in terms of complication rates, and strict adherence to meticulous insertion policies may effectively reduce catheter‐related complications.